Dubbing Method and Learning Videos for Improving Students' English Speaking - Amir Hamzah; Nareswari Nisita; Abdul Karim; Laura Thea Esmeralda (Indonesia Technology-Enhanced Language Learning (iTELL) Journal, 2025)
Many students continue to perceive English as a challenging language to master. Furthermore, they often lack confidence and fear making errors. This study aimed to assess students' English speaking skills following the implementation of the dubbing method and the use of video learning materials. The research employed a pre-post-test experimental design involving a single group. Data collection and analysis methodologies encompass observation, interviews, and documentation. The analysis of data is conducted through categorization and comparison, which includes the following classifications: dissatisfied category (AS), moderate category (F), good category (G), very good category (VG), and excellent category (E). The findings from the pre-test indicated that there were 7 students in the US category, 21 in the F category, 13 in the G category, 3 in the VG category, and none in the E category. In contrast, the post-test results revealed no students in the US category, 6 in the F category, 20 in the G category, 17 in the VG category, and 1 in the E category. The positive impact of employing the dubbing method is evident in the enhancement of students' English speaking abilities. This is supported by the pre-test results, which showed students in the US category, a category that was absent in the post-test results. Additionally, no students were found in the E and AS categories in the post-test. Therefore, the dubbing method proves to be an effective strategy in the educational process for improving students' proficiency in spoken English.